2015
DOI: 10.1016/j.apjtb.2015.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Plantago major treatment enhanced innate antioxidant activity in experimental acetaminophen toxicity

Abstract: A B S T R A C TObjective: To determine the effect of Plantago major (P. major) extract on the liver injury following acetaminophen (APAP) toxicity. Methods: The male Sprague Dawley rats (n = 38) were randomly divided into normal control (n = 6) and experiment (n = 32) groups. The latter was subdivided into four groups and induced with APAP (1 000 mg/kg) per oral, followed by P. major extract and N-acetylcysteine orally to the respective groups for six days. Results: On the seventh day, the serum bilirubin, liv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
1
7
0
Order By: Relevance
“…APAP oxidation in the liver produces a number of oxidative stress ROS products, such as superoxide anion radicals, hydroxyethyl radicals, OH -, and H 2 O 2 . The accumulation of H 2 O 2 exacerbates cell injury via lipid peroxidation, and MDA is a reliable biomarker of lipid peroxidation [19]. In the present study, APAP-induced toxicity increased MDA and H 2 O 2 levels in liver tissue as compared to the normal group.…”
Section: Discussionsupporting
confidence: 47%
“…APAP oxidation in the liver produces a number of oxidative stress ROS products, such as superoxide anion radicals, hydroxyethyl radicals, OH -, and H 2 O 2 . The accumulation of H 2 O 2 exacerbates cell injury via lipid peroxidation, and MDA is a reliable biomarker of lipid peroxidation [19]. In the present study, APAP-induced toxicity increased MDA and H 2 O 2 levels in liver tissue as compared to the normal group.…”
Section: Discussionsupporting
confidence: 47%
“…P. major showed potent antioxidant activity. Natural products with antioxidant properties showed hepatoprotective activity against some liver toxicity [ 37 ]. Turel et al indicated the protective effects of P. major on liver cells in mice poisoned by carbon tetrachloride [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…These results are in agreement with Atta et al (2006) and Turel et al (2009) they reported that P. major has a hepatoprotective effect when administered prior to CCl4 exposure. While, Hussan et al (2015) reported that administration of P. major after rat liver injury exposed to acetaminophen reduced this damage.…”
Section: Cytogenetic Studies Abnormalities In Bone Marrow (Somatic) Amentioning
confidence: 97%
“…Methanolic and ethanolic extracts of P. major have potential to be used as an alternative or adjunct treatment to reduce inflammation-mediated cell injury following APAP toxicity (Hussan et al, 2015). P. major is one of the most studied plants.…”
Section: Cytogenetic Studies Abnormalities In Bone Marrow (Somatic) Amentioning
confidence: 99%
See 1 more Smart Citation